Chemical Characterization and Antimicrobial Activity of Essential Oils and Nanoemulsions of Eugenia uniflora and Psidium guajava - Rebeca Dias dos Santos; Breno Noronha Matos; Daniel Oliveira Freire; Franklyn Santos da Silva; Bruno Alcântara do Prado; Karolina Oliveira Gomes; Marta Oliveira de Araújo; Carla Azevedo Bilac; Letícia Fernandes Silva Rodrigues; Izabel Cristina Rodrigues da Silva; Lívia Cristina Lira de Sá Barreto; Claudio Augusto Gomes da Camara; et al. (Antibiotics)
Background/Objectives: This study aimed to develop gel nanoemulsions (NEs) of Brazilian essential oils (EOs) from Eugenia uniflora and Psidium guajava, as well as to perform chemical characterization and investigate the antimicrobial activity of the EOs and NEs. Results/Conclusions: The main chemical compounds of E. uniflora EO were curzerene (34.80%) and germacrene B (11.92%), while those of P. guajava EO were β-caryophyllene (25.92%), β-selinene (22.64%), and γ-selinene (19.13%). The NEs of E. uniflora and P. guajava had droplet sizes of 105.30 and 99.50 nm and polydispersity index (PDI) values of 0.32 and 0.43, respectively. The NEs remained stable for 30 days of storage at 25 °C, with droplet sizes of 104.7 and 103.8 nm, PDI values below 0.50, and no phase separation. The NE of E. uniflora exhibited inhibition zones ranging from 8.41 to 15.13 mm against the Gram-positive bacterium Staphylococcus aureus and the Gram-negative bacteria Pseudomonas aeruginosa, Klebsiella pneumoniae, and Acinetobacter baumannii. Additionally, the NE of E. uniflora showed the largest inhibition zones against Candida albicans (20.97 mm) and Candida krusei (15.20 mm), along with low minimum inhibitory concentration (MIC) values (0.54–1.22 mg/mL) and minimal bactericidal concentration (MBC) values (4.84–11.02 mg/mL) against these pathogenic yeasts. The NE of P. guajava demonstrated low MIC (1.26 mg/mL) and MBC (11.35 mg/mL) values for C. krusei. The time–growth inhibition assay also suggests the effectiveness of the NE against the tested pathogens S. aureus and E. coli, highlighting its potential as a novel alternative therapeutic agent.